Concepts and measurement of poverty - Scott, Wolf (UN Research Institute for Social Development GenevaCH, 1981)
Presents empirical data showing the arbitrary nature of poverty lines and the imprecise and relative nature of the concept itself. Suggests how data on poverty could be improved. Shows that our thinking about poverty and how to measure it has progressed very little, if at all, since the latter part of the 19th century.